2023
DOI: 10.1088/2516-1075/acba6e
|View full text |Cite
|
Sign up to set email alerts
|

Covalency modulation enables stable Na-rich layered oxide cathodes for Na-ion batteries

Abstract: As the analogs of Li-rich materials, Na-rich transition metal layered oxides are promising cathode materials for Na-ion batteries owing to their high theoretical capacity and energy density through cumulative cationic and anionic redox. However, most of the reported Na-rich cathode materials are mainly Ru- and Ir-based layered oxides, which limits the practical application. Herein, we report a Na-rich and Ru-doped O3-type Na1.1Ni0.35Mn0.55O2 cathode to mitigate this issue. By partially substituting Mn4+ with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…10,41 During the charge process, no new peaks can be found in NMMO until 4.2 V (Figure 4a), suggesting a single-phase reaction during this region. With the 43,44 Notably, the characteristic peak of the Mg 2+ /Mn 4+ honeycomb ordering arrangement in NMMO disappears at the end of charge and reappears during the following discharge with a reduced magnitude. As reported previously, it is very likely that Mg 2+ migrates to the tetrahedral and octahedral sites in the Na + layers accompanied with the formation of Mg 2+ vacancies in the TM layers, which could induce the in-plane disorder of Mn 4+ with the disappearance of honeycomb ordering during the charge process.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10,41 During the charge process, no new peaks can be found in NMMO until 4.2 V (Figure 4a), suggesting a single-phase reaction during this region. With the 43,44 Notably, the characteristic peak of the Mg 2+ /Mn 4+ honeycomb ordering arrangement in NMMO disappears at the end of charge and reappears during the following discharge with a reduced magnitude. As reported previously, it is very likely that Mg 2+ migrates to the tetrahedral and octahedral sites in the Na + layers accompanied with the formation of Mg 2+ vacancies in the TM layers, which could induce the in-plane disorder of Mn 4+ with the disappearance of honeycomb ordering during the charge process.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…It has been suggested that the anisotropy change of TM–O bonds is the main reason to cause the excessive glide of TMO 2 layers during the charge process. Herein, the incorporation of Ru into TM sites is competent in constructing stable TM–O lattice integrity by retuning the anisotropy change of TM–O bonds through the robust Ru–O covalent bonds, thus suppressing the notorious phase transition. , …”
Section: Resultsmentioning
confidence: 99%